Examining the Role of Civil Society Organizations (CSOs) in Promoting Participatory Local Governance at the Grassroots in Bangladesh: A Case Study of Jhilongjha Union in Coxs Bazar District - Bhuiyan, Md Imran Hossain; Rumi, Maruf Hasan; Mesbah, Tamanna Binte; Rahman, Dalia (Department of Government Studies, Universitas Syiah Kuala, 2023)
This study assesses the degree to what extent civil society organizations (CSOs) can make the local governments decision-making more inclusive and participatory to meet the demands of citizens at the grassroots in Bangladesh. The study specifically explores the role of CSOs in mobilizing public engagement and affecting decision-making to promote participatory governance at the Jhilongjha union parishad, the lowest tier of local government, in Bangladesh. By utilizing qualitative research approach, this paper reveals that the CSOs are not very instrumental in establishing participatory governance in the study location. The participatory avenues at the grassroots like village court, ward meetings, and open budgeting are found to be running without expected level of peoples participation. The reasons behind the CSOs failure in promoting participatory local governance in this context include high power distance culture, adverse political environment, lack of education among citizens, and distrust among the citizens regarding local government.